Intra-oceanic subduction in the southeastern Paleo-Asian ocean: Evidence from early Permian gabbro of the Diyanmiao ophiolite in central Inner Mongolia, North China - Zhang, Xiawei; Li, Yingjie; Wang, Genhou; Wang, Shuai; Kong, Xingrui; Wang, Xiaodong; Liu, Zhibin (Frontiers in Earth Science, 2023)
Investigation of intra-oceanic subduction can improve our understanding of plate tectonic processes and the history of continental growth. Evidence for intra-oceanic subduction in the Paleo-Asian Ocean has recently become an important focus of research, including the Diyanmiao ophiolite in central Inner Mongolia, North China. Here, we report a newly discovered occurrence of early Permian gabbro in the Diyanmiao ophiolite zone. The gabbro yields a weighted mean zircon U–Pb age of 294.4 ± 2.2 Ma. The gabbro samples are characterized by moderate SiO2 (47.32–50.51 wt.%), low TiO2 (0.26–0.54 wt.%) and K2O (0.04–0.75 wt.%), and high Na2O (1.84–4.52 wt.%) contents, high Na2O/K2O ratios (2.92–58.29), and depleted chondrite-normalized light rare earth element patterns that are similar to N-MORB. The gabbros show slightly lower contents of high-field-strength elements (e.g., Nb, Ta, and Ti) and slightly higher contents of large-ion lithophile elements (e.g., K, Rb, Ba, and U) relative to N-MORB. In addition, the gabbros show high εNd(t) values (8.0–9.8) that are similar to those of forearc basalt in the Diyanmiao ophiolite and N-MORB. Integrating these new data with available results for ophiolite and arc-magmatic rocks of central Inner Mongolia, we propose that the studied gabbro was formed during the initial stage of intra-oceanic subduction and that the Paleo-Asian Ocean was still in a subduction setting during the early Permian.